Oxidative removal of oxytetracycline by UV-C/hydrogen peroxide and UV-C/peroxymonosulfate: Process optimization, kinetics, influence of co-existing ions, and quenching experiments. (December 2022) - Varank, Gamze; Can-Güven, Emine; Yazici Guvenc, Senem; Garazade, Narmin; Turk, Oruc Kaan; Demir, Ahmet; Cakmakci, Mehmet
Abstract: Oxytetracycline (OTC) is a tetracycline group antibiotic with high environmental pollution potential and is resistant to conventional treatment processes. This study provides an environmentally friendly and efficient OTC treatment by ultraviolet (UV)-based advanced oxidation processes. UV irradiation was used for the activation of hydrogen peroxide (HP) and peroxymonosulfate (PMS). In the first stage of the study, control experiments were conducted and the effect of initial pH on the UV/HP and UV/PMS in OTC removal was evaluated. In the following part, variables of the UV/HP and UV/PMS were optimized by the Box-Behnken design. The optimum conditions of the UV/HP process were as follows: 6.5 mg/L initial OTC concentration, 3.50 mM HP dose, and 45.4 min reaction time. The optimum parameters of the UV/PMS process were: 5 mg/L initial OTC concentration, 3.69 mM PMS dose, and 42.75 min reaction time. 72.8 % and 50.96 % OTC removal efficiency were achieved with the validation experiments by the UV/PMS and UV/HP processes, respectively. Kinetic studies showed that Cl − and HCO3 − ions have a positive effect whereas SO4 2− has a negligible effect on the reaction rate of both processes. NO3 − has a positive effect on the UV/HP process and a negligible effect on the UV/PMS process. According to the radical scavenging experiments, hydroxyl radicals were dominant in the UV/HP process while in the UV/PMS process both hydroxyl and sulfate radicals were involved. Both processes were effective in OTC removal; however, the UV/PMS process is more efficient and cost-effective. Graphical abstract: Unlabelled Image Highlights: UV-based advanced oxidation processes were used to treat OTC from water. The optimum pH was 9 and 11 for the UV/HP and UV/PMS processes, respectively. Removal efficiency with UV/PMS and UV/HP was 72.8 % and 50.96 %, respectively. Cl − and HCO3 − ions have a positive effect on the reaction rate. The UV/PMS process was more efficient and cost-effective.